A comparative study of tree community structure and natural regeneration status in Bontang urban forest and conservation forest of the LNG Industrial Plant Area, East Kalimantan, Indonesia - Sudrajat Sudrajat sudrajat; MINTORO DWIPUTRO (Society for Indonesian Biodiversity, 2019)
Abstract. Sudrajat S, Dwiputro M. 2019. A comparative study of tree community structure and natural regeneration status in Bontang urban forest and conservation forest of the LNG Industrial Plant Area, East Kalimantan, Indonesia. Biodiversitas 20: 2841-2847. The objective of this study was to describe and compare the community structure and natural regeneration status of tree species in urban forests within industrial estates. This study was conducted in two types of forests, Bontang urban forests within industrial area and conservation forests in the Industrial buffer zone area. At each forest location, a transect was made, and along the transect, a plot of size 20 x 20 meters was made with a distance between plots of 100 meters. In each plot, several subplots were made with size of 5m x 5m for sapling level, and 2m x 2m for seedling level. The results of this study showed that in urban forest areas there were 32 tree-level species, 21 sapling species and 15 seedling species, belonging of 49 genera and 39 families. The number of species, species richness, species diversity, evenness of sapling and tree-level species was more in urban forests than in conservation forest, and the condition was vice versa for seedling level. The value of species dominance index in conservation forest was greater than urban forest, and conversely, the value of individual density/ha for tree-level was 562.50 individuals/ha, sapling level was 7,933 ind./Ha and for seeding level 80,625 ind./ha. Of the 53 urban forest species, 28 species (52.83%) were in no regeneration category, 3 species (5.66%) were in poor regeneration category, and 22 species (41.50%) were in the new species category. In contrast, among 76 species of the conservation forests, 8 species (10.52%) showed good regeneration status, 13 species (17.10%) showed poor status and 55 species (72.36%) showed no regeneration status. From the results, it can be concluded that the Bontang urban forest in the industrial area shows no regeneration status and the emergence of new species. In the context of conservation, it is recommended to implement special silvicultural techniques to maintain the biodiversity of this urban forest.